Characterization of Catalytic Porous Medium Using Platinum for Micro-combustion Application - Miskam, Muhamad Azman; Hassan, Suhaimi; Zainal Alauddin, Zainal Alimuddin; Ishak, Mohammad Zulfikar (EDP Sciences, 2014)
In this study, catalytic alumina porous medium has been fabricated by using platinum as an active material for micro-combustion application. Platinum has been deposited onto porous medium surface via wet impregnation method. The porous medium undergoes surface modification process via wash coating method using gamma alumina (γ-Al2O3) solution, before being impregnated with platinum in order to increase the surface area. The surface morphology of porous medium entirely changes from smooth “solid-rock” into rough “sand-like” after the wash coating process. The amount of platinum deposited onto the treated porous medium is 1.66 wt.%. LPG combustion analysis shows that the combustion is successfully occur inside the catalytic porous media with overall efficiency of 71%.